Stereotactic body proton therapy for liver tumors: Dosimetric advantages and their radiobiological and clinical implications. (October 2018) - Arscott, W. Tristram; Thompson, Reid F.; Yin, Lingshu; Burgdorf, Brendan; Kirk, Maura; Ben-Josef, Edgar
Abstract: Background and Purpose: Photon Stereotactic Body Radiotherapy (SBRT) for primary and metastatic tumors of the liver is challenging for larger lesions. An in silico comparison of paired SBRT and Stereotactic Body Proton Therapy (SBPT) plans was performed to understand the potential advantages of SBPT as a function of tumor size and location. Methods and materials: Theoretical tumor volumes with maximum diameter of 1–10 cm were contoured in the dome, right inferior, left medial, and central locations. SBRT and SBPT plans were generated to deliver 50 Gy in 5 fractions, max dose <135%. When organs-at-risk (OAR) constraints were exceeded, hypothetical plans (not clinically acceptable) were generated for comparison. Liver normal tissue complication probability (NTCP) models were applied to evaluate differences between treatment modalities. Results: SBRT and SBPT were able to meet target goals and OAR constraints for lesions up to 7 cm and 9 cm diameter, respectively. SBPT plans resulted in a higher integral gross target dose for all lesions up to 7 cm (mean dose 57.8 ± 2.3 Gy to 64.1 ± 2.2 Gy, p  < 0.01). Simultaneously, SBPT spared dose to the uninvolved liver in all locations (from 11.5 ± 5.3 Gy to 8.6 ± 4.4 Gy, p  < 0.01), resulting in lower NTCP particularly for larger targets in the dome and central locations. SBPT also spared duodenal dose across all sizes and positions (from 7.3 ± 1.1 Gy to 1.1 ± 0.3 Gy, p  < 0.05). Conclusion: The main advantages of SBPT over SBRT is meeting plan goals and constrains for larger targets, particularly dome and central locations, and sparing dose to uninvolved liver. For such patients, SBPT may allow improvements in tumor control and treatment safety.